(untitled) (Medicine Today, 2014)
Trigeminal neuralgia is a sudden, severe, stabbing, recurrent and usually unilateral pain in the distribution of one or more branches of the fifth cranial nerve. A 55 years old man, diagnosed case of Trigeminal Neuralgia of the left side of the face was treated with oral carbamazepine with good response. But after that the disease became refractory to the drug. With the titration of dose of carbamazepine, raising up to 1200 mg daily in three equal divided doses added with amitryptylene, we could give relief of pain to patient. The patient is now under observation & we are following him for last 6 months with a good response of the combination drug. It justifies that alteration, titration of carbamazepine and combination with amitryptylene can cause remission of trigeminal neuralgia instead of doing surgical intervention. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21319 Medicine Today 2014 Vol.26(1): 66-68